Biodegradable composite polylactic acid packaging bag and preparation method thereof

Through the composite technology of modified polylactic acid, modified starch and modified nanofiber, composite polylactic acid packaging bags with high mechanical properties, heat resistance and rapid biodegradation were prepared, solving the shortcomings of existing polylactic acid materials in terms of mechanical properties, heat resistance and degradation rate.

CN119529513AInactive Publication Date: 2025-02-28ANHUI YUNMING NEW MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411860971.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polylactic acid materials cannot fully meet the high requirements of packaging materials in terms of mechanical properties, heat resistance and degradation rate of the express delivery and logistics industries.

Method used

Modified polylactic acid, modified starch, modified nanofibers, pigments and additives are used as the main materials to prepare composite polylactic acid packaging bags through textile flat wire and warp weft knitting technology. Modified polylactic acid enhances its high temperature resistance and biodegradation properties through multi-block copolymerization and cross-linking technology, and modified starch and modified nanofibers improve the toughness and strength of the material.

Benefits of technology

It significantly improves the physical properties, high temperature resistance and biodegradation properties of packaging bags, and can quickly decompose in the natural environment and reduce environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193193130000031
    Figure BDA0005193193130000031
  • Figure BDA0005193193130000171
    Figure BDA0005193193130000171
  • Figure BDA0005193193130000172
    Figure BDA0005193193130000172
Patent Text Reader

Abstract

The invention discloses a biodegradable composite polylactic acid packaging bag and a preparation method thereof, belongs to the technical field of biodegradable materials, and aims to solve the technical problem that the mechanical property, heat resistance and biodegradation rate of a polylactic acid material in the prior art need to be further improved. The material comprises the following components in parts by weight: 90-100 parts of modified polylactic acid, 10-15 parts of modified starch, 15-20 parts of modified nanofiber, 4-8 parts of pigment and 5-7 parts of additive, and is prepared by taking the modified polylactic acid as a basic raw material, the modified starch and the modified nanofiber as reinforcing materials and the pigment and the additive as auxiliary additives. The mechanical strength and high temperature resistance of the packaging bag are effectively improved, and the biodegradability of the packaging bag is improved, so that the packaging bag better meets the requirements of express and logistics industries on biodegradable packaging materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biodegradable materials, and in particular to a biodegradable composite polylactic acid packaging bag and a preparation method thereof. Background Art

[0002] With the booming development of global e-commerce and the rapid growth of the logistics industry, the demand for packaging materials by express delivery and logistics companies such as China Post, JD.com, and SF Express has increased dramatically. Traditional plastic packaging bags are widely used in the express delivery and logistics industries due to their low cost, waterproof and moisture-proof properties. However, after completing their packaging mission, these plastic packaging bags are often discarded at will and become difficult-to-degrade environmental pollutants, causing serious damage to the soil, water sources and ecosystems. In order to respond to the global call for environmental protection, reduce plastic pollution, and develop biodegradable packaging materials has become an industry consensus.

[0003] In the prior art, a Chinese invention patent with publication number CN108586934A discloses a biodegradable PP woven bag material, including the following parts by weight: polypropylene: 100-200 parts, natto bacteria: 0.1-0.5 parts, corn starch: 1-10 parts, and a compatibilizer: 0.5-1 parts. Natto bacteria powder and corn starch are added. Natto bacteria exist in the natto bacteria powder, and the natto bacteria itself secretes a substance to decompose the corn starch. In the whole material preparation process, the corn starch first polymerizes with the polypropylene, serving as a bridge to connect the polypropylene molecules. At the same time, the natto bacteria powder will also polymerize therein. In the process of burying in the soil, due to the presence of the natto bacteria powder, it can induce the degradation of the corn starch molecules, so that the entire molecular chain is broken, and the large molecular polypropylene is decomposed into small molecular polypropylene, which is more conducive to the degradation of the entire polymer.

[0004] However, it takes about 20-30 years for polypropylene to degrade in the natural environment, and toxins will be released in the process, so it cannot be said to be biodegradable. Polylactic acid, as a bio-based material derived from renewable resources, has great potential in the field of degradable packaging materials due to its good biocompatibility, degradability and processability. Although polylactic acid has certain mechanical strength, compared with traditional petroleum-based plastics, its toughness, impact resistance and wear resistance are still insufficient. The low glass transition temperature of polylactic acid makes it easy to deform or lose strength under high temperature conditions, which makes polylactic acid difficult to use in packaging occasions that need to withstand high temperature or heat treatment. In addition, the biodegradation rate of polylactic acid is affected by many factors such as environmental temperature, humidity, and microbial species. In the natural environment, it takes a long time for polylactic acid packaging waste to biodegrade in the environment, resulting in polylactic acid materials in terms of mechanical properties, heat resistance and degradation rate. Can not fully meet the high requirements of the express and logistics industry for packaging materials.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide a biodegradable composite polylactic acid packaging bag and a preparation method thereof, so as to solve the technical problem that the polylactic acid materials in the prior art cannot fully meet the high requirements of the express and logistics industries for packaging materials in terms of mechanical properties, heat resistance and degradation rate.

[0007] The object of the present invention can be achieved by the following technical scheme: a biodegradable composite polylactic acid packaging bag, comprising the following components in parts by weight: 90-100 parts of modified polylactic acid, 10-15 parts of modified starch, 15-20 parts of modified nanofibers, 4-8 parts of pigments and 5-7 parts of additives;

[0008] The preparation method of the modified polylactic acid is as follows: L-lactide, polyethylene glycol, hexamethyl-1,15-dihydroxyoctasiloxane, toluene and a catalyst are added into a nitrogen-protected reactor and stirred, the jacket temperature of the reactor is increased to 120-130° C., the reactor is kept warm for reaction for 8-10 hours, the reactor temperature is reduced to 75-85° C., isophorone diisocyanate is added into the reactor, the reactor is kept warm for 3-4 hours, and the modified polylactic acid is obtained by post-processing.

[0009] The synthetic reaction equation of modified polylactic acid is:

[0010]

[0011] Where:

[0012] R1:

[0013] R2:

[0014] The synthetic reaction mechanism of modified polylactic acid is:

[0015] L-lactide undergoes a ring-opening polymerization reaction under the catalysis of stannous octoate at high temperature and under nitrogen protection, the ring structure of L-lactide is opened to form a linear polylactic acid chain, polyethylene glycol and the terminal hydroxyl groups on the hexamethyl-1,15-dihydroxyoctasiloxane molecular chain undergo an esterification reaction with the carboxyl groups at the ends of the polylactic acid chains, thereby being introduced into the polylactic acid chains to form polylactic acid-polyethylene glycol-polylactic acid co-embedded chain segments and polylactic acid-hexamethyl-1,15-dihydroxyoctasiloxane-polylactic acid co-embedded chain segments. The two isocyanate groups contained in the isophorone diisocyanate molecule can react with the hydroxyl groups on the polylactic acid chain to extend the length of the polymer chain. By controlling the excessive use of isophorone diisocyanate, an isocyanate-terminated modified polylactic acid is formed. The isocyanate groups form amino groups in a water environment. The impurities of the small molecule structure are removed by high-temperature reduced-pressure distillation to prepare the modified polylactic acid.

[0016] Furthermore, the amount ratio of L-lactide, polyethylene glycol, hexamethyl-1,15-dihydroxyoctasiloxane, toluene, catalyst and isophorone diisocyanate is 28-32g:5-7g:8-10g:300mL:0.5g:6-8g, the catalyst is stannous octoate, and the polyethylene glycol is polyethylene glycol 200. The post-treatment includes: after the reaction is completed, adding purified water to the reactor, raising the temperature of the reactor to 120-130°C, and distilling under reduced pressure until no liquid is produced to obtain modified polylactic acid.

[0017] Furthermore, the preparation method of the modified starch is: adding starch and glycerol into a torque rheometer at a temperature of 120-130° C., setting the stirring speed to 70-80 r / min, heat preservation for 15-25 min, cooling and discharging, and obtaining the modified starch.

[0018] The synthetic reaction mechanism of modified starch is:

[0019] At high temperatures, starch granules begin to soften and partially gelatinize, and the structure of the starch granules becomes looser. Glycerol, as a small molecule polyol, has good permeability, making it easier for glycerol molecules to penetrate into the starch granules. The infiltrated glycerol molecules can occupy part of the space in the starch granules, increasing the swelling of the starch granules. In addition, hydrogen bonds are easily formed between the hydroxyl groups on the glycerol molecules and the hydroxyl groups on the starch molecules under the action of high temperature. The formation of hydrogen bonds can enhance the interaction between glycerol and starch molecules, making the two more closely combined to prepare modified starch.

[0020] Furthermore, the weight ratio of the starch to glycerol is 7:2-3, and the starch is one or more of sweet potato starch, potato starch, and cassava starch.

[0021] Further, the modified nanofibers are processed by the following steps:

[0022] A1, adding sawdust fiber, chitosan and purified water into a ball mill, ball milling for 60-80 minutes, transferring it to a high-pressure homogenizer, homogenizing it for 8-10 times, and post-processing to obtain composite nanofibers;

[0023] The synthetic reaction mechanism of composite nanofibers is:

[0024] Sawdust fiber and chitosan are mixed evenly in a ball mill. The ball milling medium exerts strong mechanical impact and shear force on the raw materials, which promotes the crushing and refinement of the raw material particles, and at the same time promotes the physical mixing of different components, so that they are embedded or intertwined with each other to a certain extent to form a tighter mixture. The high-pressure homogenizer further refines the particles through high-pressure shear, impact and cavitation effects, so that the mixture reaches nano-level dispersion, and at the same time enhances the interaction between the components to prepare composite nanofibers.

[0025] A2. Add the composite nanofibers, anhydrous ethanol and KH-560 into a reactor and stir. The temperature of the reactor is raised to 50-60° C., and sodium hydroxide solution is added into the reactor. The reaction is kept warm for 2-3 hours, and the modified nanofibers are obtained by post-treatment.

[0026] The synthetic reaction mechanism of modified nanofibers is:

[0027] The KH-560 molecule contains hydrolyzable siloxane groups and organic functional groups. Under alkaline conditions, the siloxane groups are hydrolyzed to generate silanols, which react with the hydroxyl groups on the surface of the composite nanofibers to form covalent bonds, forming KH-560 modifications on the outside of the composite nanofibers to obtain modified nanofibers.

[0028] Furthermore, in step A1, the amount ratio of the sawdust fiber, chitosan and purified water is 5g:3g:20mL, and the post-treatment includes: after the treatment is completed, taking it out from the homogenizer, placing it in a freeze dryer at a temperature of -20°C, and freeze-drying it to constant weight to obtain composite nanofibers; in step A2, the amount ratio of the composite nanofibers, anhydrous ethanol, KH-560 and sodium hydroxide solution is 7g:30mL:3g:10mL, and the concentration of the sodium hydroxide solution is 0.3-0.5mol / L, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with ethanol twice and then dried, and the filter cake is transferred to a drying oven at a temperature of 45-55°C, and dried to constant weight to obtain modified nanofibers.

[0029] Further, the wood fiber is processed by the following steps:

[0030] B1. Circulate and extract the sawdust using an extracting liquid at a temperature of 50-60°C for 6-8 hours, and then post-treat the sawdust to obtain pre-treated sawdust;

[0031] B2, adding the pretreated sawdust, purified water and mixed acid into a nitrogen-protected reactor and stirring, raising the reactor temperature to 70-80°C, and heat-insulating for 6-8h, adding supplementary acid to the reactor once every 50-60min during the heat-insulating stage, and post-treating to obtain acid-treated sawdust;

[0032] B3, adding acid-treated sawdust and alkali solution into a reactor and stirring, raising the temperature of the reactor to 85-95°C, keeping the temperature and stirring for 3-4 hours, and post-treating to obtain sawdust fiber precursor;

[0033] B4. Repeat steps B2-B3 to cyclically treat the sawdust fiber precursor 3-4 times to obtain sawdust fibers.

[0034] The synthetic reaction mechanism of sawdust fiber is:

[0035] Toluene and methanol are used as organic solvents to dissolve and extract non-polar oil and resin components in sawdust to prepare pretreated sawdust. Acetic acid is used to provide acidic conditions to increase the strong oxidizing property of sodium chlorite, oxidize phenolic hydroxyl groups and other active groups in lignin, promote the breakage and degradation of lignin molecular chains, and dissolve lignin from sawdust. At the same time, part of hemicellulose is also degraded. Potassium hydroxide is used as a strong base to destroy the ester bonds and ether bonds between lignin and hemicellulose, and dissolve lignin from sawdust. Through acid-base cycle treatment, impurities and residual lignin / hemicellulose in sawdust are further removed to obtain cellulose-rich sawdust fibers.

[0036] Further, in step B1, the ratio of sawdust to extract is 1g:10-15mL, the extract is composed of toluene and methanol in a volume ratio of 5:3, and the post-treatment includes: after the reaction is completed, suction filtration, washing the filter cake with methanol twice and then drying, transferring the filter cake to a drying oven at a temperature of 50-60°C, and drying to constant weight to obtain pretreated sawdust; in step B2, the ratio of the pretreated sawdust, purified water, mixed acid and supplementary acid is 5g:150mL:3g:3g, and the mixed acid and supplementary acid are both sodium chlorite and 80wt% acetic acid aqueous solution by weight. The amount ratio of the acid-treated sawdust and the alkali solution is 1g:15mL, and the alkali solution is 4-7wt% potassium hydroxide aqueous solution. The post-treatment includes: after the reaction is completed, suction filtration, washing the filter cake with purified water until it is neutral and then drying it, transferring the filter cake to a drying oven at a temperature of 70-80°C, and drying it to constant weight to obtain acid-treated sawdust; in step B3, the amount ratio of the acid-treated sawdust and the alkali solution is 1g:15mL, and the alkali solution is a 4-7wt% potassium hydroxide aqueous solution. The post-treatment includes: after the reaction is completed, suction filtration, washing the filter cake with purified water until it is neutral and then drying it, transferring the filter cake to a drying oven at a temperature of 70-80°C, and drying it to constant weight to obtain a sawdust fiber precursor.

[0037] The present invention also provides a method for preparing a biodegradable composite polylactic acid packaging bag, comprising the following steps:

[0038] S1, adding modified polylactic acid, modified starch, modified nanofiber, pigment and additives into a flat yarn machine, heating and plasticizing through a material pipe, extruding and stretching, and obtaining a textile flat yarn;

[0039] S2, adding the textile flat yarn into a weaving machine for warp and weft weaving to obtain a packaging bag blank, and performing slitting and sewing operations on the bottom opening of the packaging bag blank to obtain a packaging bag.

[0040] Furthermore, in step S1, the additive is composed of a dispersant, an antioxidant, a light stabilizer, an antistatic agent, and a plasticizer in a weight ratio of 2:1:2:1:4, the dispersant is stearate, the antioxidant is one or more of antioxidant 168, antioxidant 364, and antioxidant 1010, the light stabilizer is one or more of UV-944, UV-770, and UV-783, the antistatic agent is sodium p-nonylphenoxypropyl sulfonate, and the plasticizer is phthalate. The temperatures of the eight temperature sections of the material pipe of the flat wire machine from the feed end to the discharge end are 175-185°C, 180-190°C, 185-195°C, 185-195°C, 185-195°C, 185-195°C, 190-200°C, and 190-200°C, respectively, and the stretching ratio is 5-7 times.

[0041] The present invention has the following beneficial effects:

[0042] 1. The biodegradable composite polylactic acid packaging bag of the present invention is prepared by using modified polylactic acid as a basic raw material, modified starch and modified nanofibers as reinforcing materials, and pigments and additives as auxiliary additives. After preparing textile flat yarns, the packaging bag is prepared by weaving operation. KH-560 modifies the prepared nanofibers after the wood chip fibers and chitosan are composited, which not only optimizes the fiber structure of the wood chip fibers and improves the interaction between the fibers, but also enhances the bonding force between the materials, increases the crosslinking degree between molecules, and improves the physical properties of the packaging bag. The modified polylactic acid is synthesized by multi-block copolymerization, and the modified polylactic acid is composited with the nanofibers, which also improves the high temperature resistance and biodegradability of the packaging bag.

[0043] 2. The biodegradable composite polylactic acid packaging bag of the present invention is prepared by preparing wood chip fibers rich in cellulose, and then reinforcing and modifying the fibers with chitosan to prepare composite nanofibers, and then coating the fibers with KH-560 to obtain modified nanofibers. The wood chip fibers are pretreated and acid-treated, and their fiber structure is optimized, and the bonding force between the fibers is enhanced. Chitosan, as a natural polymer material, has good mechanical properties. The composite of chitosan further enhances the strength and toughness of the fibers, so that the packaging bag is not easy to break when stretched. KH-560, as a silane coupling agent, is coated on the outside of the composite nanofibers to enhance the interfacial bonding force between the fibers and the modified starch and the polylactic acid matrix. The enhanced interfacial bonding force helps to more effectively disperse the tensile stress throughout the material, thereby further increasing the tensile load of the packaging bag. Glycerol-modified enhanced starch The prepared modified starch has a looser and more elastic structure of starch particles due to the penetration and expansion of glycerol molecules. This structural characteristic can absorb more energy when the packaging bag is stretched, delay the occurrence of fracture, and thus improve the toughness of the packaging bag; the abundant hydrogen bonds between the glycerol molecules and the starch can resist the damage of thermal stress and prevent the material from softening, deforming or breaking, so that the entire modified starch system can maintain good integrity at high temperatures, and the abundant hydroxyl groups on the modified starch can be interwoven and entangled with the modified nanofibers to form a complex network structure, construct a strong skeleton, improve the tensile strength and tear strength of the packaging bag, and then improve the physical properties of the packaging bag. The fibers and starch molecules in the network structure are closely arranged to form a dense barrier to block the direct transfer of heat and reduce the temperature rise rate inside the packaging bag.

[0044] 3. The biodegradable composite polylactic acid packaging bag of the present invention is a modified polylactic acid prepared by multi-block copolymerization and cross-linking of polylactic acid, polyethylene glycol, and hexamethyl-1,15-dihydroxyoctasiloxane using isophorone diisocyanate as a cross-linking agent; the introduction of polyethylene glycol and hexamethyl-1,15-dihydroxyoctasiloxane forms a co-block segment, the addition of isophorone diisocyanate allows the polylactic acid chain to be extended to form a cross-linked structure, thereby enhancing the interaction force between the molecular chains and improving the tensile strength and toughness thereof; the polyethylene glycol introduced into the modified polylactic acid can not only interact with the polylactic acid molecular chain to form a more complex network structure, but also can exist as a degradable material to improve the biodegradability of the material; the introduction of hexamethyl-1,15-dihydroxyoctasiloxane enhances the high temperature resistance of the modified polylactic acid, thereby making the polylactic acid The polylactic acid can maintain good stability at high temperatures, reduce the thermal decomposition and degradation of polylactic acid at high temperatures, thereby improving the heat resistance of the packaging bag. The modified polylactic acid molecular chain formed by ring-opening polymerization and esterification reaction has higher rigidity. This rigid structure makes the material not easy to deform at high temperatures and maintains good dimensional stability. Sawdust fiber, chitosan and polylactic acid are all natural biodegradable materials. These materials can be decomposed by microorganisms in the natural environment and eventually converted into harmless substances. The loose internal structure of starch particles increases the specific surface area and porosity of starch particles, making it easier for microorganisms to contact the inside of starch particles, accelerating the decomposition of starch by microorganisms. The cooperation between various materials makes it easier to be biodegraded under natural soil conditions, thereby improving its biodegradability. DETAILED DESCRIPTION

[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] This embodiment provides a method for preparing a biodegradable composite polylactic acid packaging bag, comprising the following steps:

[0048] S1. Preparation of wood fiber

[0049] Toluene and methanol were mixed evenly in a volume ratio of 5:3 to obtain an extract;

[0050] Sawdust and extractant were added into an extractor at a temperature of 50°C at a ratio of 1g:10mL, and the extraction was circulated for 6 hours. The temperature of the extractor was lowered to room temperature, and the filter cake was filtered. The filter cake was washed with methanol twice and then dried. The filter cake was transferred to a drying oven at a temperature of 50°C and dried to constant weight to obtain pretreated sawdust;

[0051] Weigh: 50 g of pretreated sawdust, 1500 mL of purified water, 17.5 g of sodium chlorite and 12.5 g of 80 wt% acetic acid aqueous solution, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 70°C, and keep it warm for 6 hours. Add 17.5 g of sodium chlorite and 12.5 g of 80 wt% acetic acid aqueous solution into the reactor at intervals of 50 minutes during the insulation treatment stage. After the reaction is completed, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, and dry it to constant weight to obtain acid-treated sawdust;

[0052] Acid-treated sawdust and 4 wt% potassium hydroxide aqueous solution were added to a reactor at a ratio of 1 g:15 mL and stirred. The temperature of the reactor was raised to 85°C and stirred for 3 hours. After the reaction was completed, the filter cake was filtered and washed with purified water until neutral and then dried. The filter cake was transferred to a drying oven at 70°C and dried to constant weight to obtain a sawdust fiber precursor.

[0053] The above-mentioned steps of pre-treating sawdust to prepare sawdust fiber precursor are repeated, and the sawdust fiber precursor is cyclically treated for 3 times to obtain sawdust fiber.

[0054] S2. Preparation of modified nanofibers

[0055] Weigh: 50 g of sawdust fiber, 30 g of chitosan and 200 mL of purified water, add them into a ball mill, ball mill for 60 min, transfer them into a high-pressure homogenizer, homogenize them 8 times, take them out of the homogenizer, place them in a freeze dryer at a temperature of -20°C, freeze-dry them to constant weight, and obtain composite nanofibers;

[0056] Weigh: 70g of composite nanofibers, 300mL of anhydrous ethanol, and 30g of KH-560, add into the reactor and stir, raise the temperature of the reactor to 50°C, add 100mL of 0.3mol / L sodium hydroxide solution into the reactor, keep warm for 2h, lower the temperature of the reactor to room temperature, filter, wash the filter cake twice with ethanol and then dry it, transfer the filter cake to a drying oven at 45°C, dry to constant weight, and obtain modified nanofibers.

[0057] S3. Preparation of modified starch

[0058] Sweet potato starch and glycerol were added into a torque rheometer at a weight ratio of 7:2 at a temperature of 120°C, the stirring speed was set to 70 r / min, the temperature was kept for 15 minutes, the temperature was lowered and the material was discharged to obtain modified starch.

[0059] S4. Preparation of modified polylactic acid

[0060] Weigh: 280 g of L-lactide, 50 g of polyethylene glycol 200, 80 g of hexamethyl-1,15-dihydroxyoctasiloxane, 3000 mL of toluene and 5 g of stannous octoate, add into a nitrogen-protected reactor and stir, raise the jacket temperature of the reactor to 120°C, keep warm for 8 hours, lower the temperature of the reactor to 75°C, add 60 g of isophorone diisocyanate into the reactor, keep warm for 3 hours, add 60 mL of purified water into the reactor, raise the temperature of the reactor to 120°C, and distill under reduced pressure until no liquid is produced to obtain modified polylactic acid.

[0061] S5, textile flat yarn

[0062] Mix sodium stearate, antioxidant 168, UV-944, sodium p-nonylphenoxypropyl sulfonate, and dimethyl phthalate in a weight ratio of 2:1:2:1:4 to obtain an additive;

[0063] Weighing by weight: 90 parts of modified polylactic acid, 10 parts of modified starch, 15 parts of modified nanofiber, 4 parts of pigment and 5 parts of additives, adding them into the flat yarn machine and entering the flat yarn machine material pipe, the temperature of the 8 temperature sections of the flat yarn machine material pipe from the feed end to the discharge end are 175°C, 180°C, 185°C, 185°C, 185°C, 185°C, 190°C, 190°C, respectively, after heating and plasticizing through the material pipe, stretching at a stretching ratio of 5 times to obtain textile flat yarn;

[0064] S6. Prepare packaging bags

[0065] The textile flat yarn is added into a weaving machine, and the warp and weft are woven according to a warp density of 40 yarns / 100 mm and a weft density of 48 yarns / 100 mm to obtain a packaging bag blank, and the packaging bag blank is cut and the bottom opening is sewn to obtain a packaging bag.

[0066] Example 2

[0067] This embodiment provides a method for preparing a biodegradable composite polylactic acid packaging bag, comprising the following steps:

[0068] S1. Preparation of wood fiber

[0069] Toluene and methanol were mixed evenly in a volume ratio of 5:3 to obtain an extract;

[0070] Sawdust and extractant were added into an extractor at a temperature of 55°C at a ratio of 1g:13mL, and the extraction was circulated for 7h. The temperature of the extractor was lowered to room temperature, and the filter cake was filtered. The filter cake was washed with methanol twice and then dried. The filter cake was transferred to a drying oven at a temperature of 55°C and dried to constant weight to obtain pretreated sawdust;

[0071] Weigh: 50 g of pretreated sawdust, 1500 mL of purified water, 17.5 g of sodium chlorite and 12.5 g of 80 wt% acetic acid aqueous solution, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 75°C, and keep it warm for 7 hours. Add 17.5 g of sodium chlorite and 12.5 g of 80 wt% acetic acid aqueous solution into the reactor at intervals of 55 minutes during the insulation treatment stage. After the reaction is completed, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at a temperature of 75°C, and dry it to constant weight to obtain acid-treated sawdust;

[0072] Acid-treated sawdust and 5 wt% potassium hydroxide aqueous solution were added to a reactor at a ratio of 1 g:15 mL and stirred. The temperature of the reactor was raised to 90° C. and stirred for 3.5 hours. After the reaction was completed, the filter cake was washed with purified water until neutral and then dried. The filter cake was transferred to a drying oven at a temperature of 75° C. and dried to constant weight to obtain a sawdust fiber precursor.

[0073] The above-mentioned steps of pre-treating sawdust to prepare sawdust fiber precursor are repeated, and the sawdust fiber precursor is cyclically treated for 3 times to obtain sawdust fiber.

[0074] S2. Preparation of modified nanofibers

[0075] Weigh: 50 g of sawdust fiber, 30 g of chitosan and 200 mL of purified water, add them into a ball mill, ball mill for 70 min, transfer them into a high-pressure homogenizer, homogenize them 9 times, take them out of the homogenizer, place them in a freeze dryer at a temperature of -20°C, freeze-dry them to constant weight, and obtain composite nanofibers;

[0076] Weigh: 70g of composite nanofibers, 300mL of anhydrous ethanol, and 30g of KH-560, add into the reactor and stir, raise the temperature of the reactor to 55°C, add 100mL of 0.4mol / L sodium hydroxide solution into the reactor, keep warm for 2.5h, lower the temperature of the reactor to room temperature, filter, wash the filter cake twice with ethanol and then dry it, transfer the filter cake to a drying oven at 50°C, dry to constant weight, and obtain modified nanofibers.

[0077] S3. Preparation of modified starch

[0078] Potato starch and glycerol were added into a torque rheometer at a weight ratio of 7:2.5 at a temperature of 125° C., the stirring speed was set to 75 r / min, the temperature was kept at 20 min, the temperature was lowered and the material was discharged to obtain modified starch.

[0079] S4. Preparation of modified polylactic acid

[0080] Weigh: 300 g of L-lactide, 60 g of polyethylene glycol 200, 90 g of hexamethyl-1,15-dihydroxyoctasiloxane, 3000 mL of toluene and 5 g of stannous octoate, add into a nitrogen-protected reactor and stir, raise the jacket temperature of the reactor to 125°C, keep warm for 9 hours, lower the temperature of the reactor to 80°C, add 70 g of isophorone diisocyanate into the reactor, keep warm for 3.5 hours, add 60 mL of purified water into the reactor, raise the temperature of the reactor to 125°C, distill under reduced pressure until no liquid is produced, and obtain modified polylactic acid.

[0081] S5, textile flat yarn

[0082] Zinc stearate, antioxidant 364, UV-770, sodium p-nonylphenoxypropyl sulfonate, and dibutyl phthalate are uniformly mixed in a weight ratio of 2:1:2:1:4 to obtain an additive;

[0083] Weighing by weight: 95 parts of modified polylactic acid, 13 parts of modified starch, 17 parts of modified nanofiber, 6 parts of pigment and 6 parts of additives, adding them into the flat yarn machine and entering the flat yarn machine material pipe, the temperature of the 8 temperature sections of the flat yarn machine material pipe from the feed end to the discharge end are 180°C, 185°C, 190°C, 190°C, 190°C, 190°C, 195°C, 195°C, respectively, after heating and plasticizing through the material pipe, stretching at a stretching ratio of 6 times to obtain textile flat yarn;

[0084] S6. Prepare packaging bags

[0085] The textile flat yarn is added into a weaving machine, and the warp and weft are woven according to a warp density of 40 yarns / 100 mm and a weft density of 48 yarns / 100 mm to obtain a packaging bag blank, and the packaging bag blank is cut and the bottom opening is sewn to obtain a packaging bag.

[0086] Example 3

[0087] This embodiment provides a method for preparing a biodegradable composite polylactic acid packaging bag, comprising the following steps:

[0088] S1. Preparation of wood fiber

[0089] Toluene and methanol were mixed evenly in a volume ratio of 5:3 to obtain an extract;

[0090] Sawdust and extractant were added into an extractor at a temperature of 60°C at a ratio of 1g:15mL, and the extraction was circulated for 8h. The temperature of the extractor was lowered to room temperature, and the filter cake was filtered. The filter cake was washed with methanol twice and then dried. The filter cake was transferred to a drying oven at a temperature of 60°C and dried to constant weight to obtain pretreated sawdust;

[0091] Weigh: 50 g of pretreated sawdust, 1500 mL of purified water, 17.5 g of sodium chlorite and 12.5 g of 80 wt% acetic acid aqueous solution, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 80°C, and keep it warm for 8 hours. Add 17.5 g of sodium chlorite and 12.5 g of 80 wt% acetic acid aqueous solution into the reactor at intervals of 60 minutes during the insulation treatment stage. After the reaction is completed, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at a temperature of 80°C, and dry it to constant weight to obtain acid-treated sawdust;

[0092] Acid-treated sawdust and 7wt% potassium hydroxide aqueous solution were added to a reactor at a ratio of 1g:15mL and stirred. The temperature of the reactor was raised to 95°C and stirred for 4 hours. After the reaction was completed, the filter cake was washed with purified water until neutral and then dried. The filter cake was transferred to a drying oven at 80°C and dried to constant weight to obtain a sawdust fiber precursor.

[0093] The above-mentioned steps of pre-treating sawdust to prepare sawdust fiber precursor are repeated, and the sawdust fiber precursor is cyclically treated 4 times to obtain sawdust fiber.

[0094] S2. Preparation of modified nanofibers

[0095] Weigh: 50 g of sawdust fiber, 30 g of chitosan and 200 mL of purified water, add them into a ball mill, ball mill for 80 min, transfer them into a high-pressure homogenizer, homogenize them 10 times, take them out of the homogenizer, place them in a freeze dryer at a temperature of -20°C, freeze-dry them to constant weight, and obtain composite nanofibers;

[0096] Weigh: 70g of composite nanofibers, 300mL of anhydrous ethanol, and 30g of KH-560, add into the reactor and stir, raise the temperature of the reactor to 60°C, add 100mL of 0.5mol / L sodium hydroxide solution into the reactor, keep warm for 3h, lower the temperature of the reactor to room temperature, filter, wash the filter cake twice with ethanol and then dry it, transfer the filter cake to a drying oven at 55°C, dry to constant weight, and obtain modified nanofibers.

[0097] S3. Preparation of modified starch

[0098] Cassava starch and glycerol were added into a torque rheometer at a weight ratio of 7:3 at a temperature of 130° C., the stirring speed was set to 80 r / min, the temperature was kept for 25 minutes, and the material was cooled and discharged to obtain modified starch.

[0099] S4. Preparation of modified polylactic acid

[0100] Weigh: 320 g of L-lactide, 70 g of polyethylene glycol 200, 100 g of hexamethyl-1,15-dihydroxyoctasiloxane, 3000 mL of toluene and 5 g of stannous octoate, add into a nitrogen-protected reactor and stir, raise the jacket temperature of the reactor to 130°C, keep warm for 10 hours, lower the temperature of the reactor to 85°C, add 80 g of isophorone diisocyanate into the reactor, keep warm for 4 hours, add 60 mL of purified water into the reactor, raise the temperature of the reactor to 130°C, distill under reduced pressure until no liquid is produced, and obtain modified polylactic acid.

[0101] S5, textile flat yarn

[0102] Barium stearate, antioxidant 1010, UV-783, sodium p-nonylphenoxypropyl sulfonate, and diethyl phthalate are uniformly mixed in a weight ratio of 2:1:2:1:4 to obtain an additive;

[0103] Weighing by weight: 100 parts of modified polylactic acid, 15 parts of modified starch, 20 parts of modified nanofiber, 8 parts of pigment and 7 parts of additives, adding them into the flat yarn machine and entering the flat yarn machine material pipe, the temperature of the flat yarn machine material pipe from the feed end to the discharge end is 185° C., 190° C., 195° C., 195° C., 195° C., 195° C., 200° C., 200° C., respectively, after heating and plasticizing through the material pipe, stretching at a stretching ratio of 7 times to obtain a textile flat yarn;

[0104] S6. Prepare packaging bags

[0105] The textile flat yarn is added into a weaving machine, and the warp and weft are woven according to a warp density of 40 yarns / 100 mm and a weft density of 48 yarns / 100 mm to obtain a packaging bag blank, and the packaging bag blank is cut and the bottom opening is sewn to obtain a packaging bag.

[0106] Comparative Example 1

[0107] The difference between this comparative example and Example 3 is that chitosan is not added in step S2.

[0108] Comparative Example 2

[0109] The difference between this comparative example and Example 3 is that step S3 is eliminated, and the modified starch in step S4 is replaced by cassava starch in step S5.

[0110] Comparative Example 3

[0111] The difference between this comparative example and Example 3 is that polyethylene glycol 200 is not added in step S4.

[0112] Comparative Example 4

[0113] The difference between this comparative example and Example 3 is that hexadecyl-1,15-dihydroxyoctasiloxane is not added in step S4.

[0114] Performance Test:

[0115] The tensile load and heat resistance of the packaging bag samples prepared in Examples 1-3 and Comparative Examples 1-4 were tested respectively with reference to the standard GB / T 8946-2013 "General Technical Requirements for Plastic Woven Bags";

[0116] Referring to the standard GB / T 41010-2021 "Degradation performance and labeling requirements of biodegradable plastics and products", the 12-week disintegration rate and 180-day biodegradation rate of the packaging bag samples prepared in Examples 1-3 and Comparative Examples 1-4 under industrial composting conditions, as well as the 180-day, 1-year and 2-year biodegradation rates under sample soil conditions, are tested. The specific test results are shown in Tables 1-2 below.

[0117] Table 1- Physical properties test data of the sample

[0118]

[0119] Table 2-Biodegradation performance test data of samples

[0120]

[0121]

[0122] Data Analysis:

[0123] Comparative analysis of the data in Tables 1-2 above shows that the radial tensile load of the biodegradable composite polylactic acid packaging bag prepared by the present invention reaches 942N / 50mm, the latitudinal tensile load reaches 881N / 50mm, and has good heat resistance. The prepared biodegradable composite polylactic acid packaging bag has a 12-week disintegration rate of 98.2% and a 180-day biodegradation rate of 94.1% under industrial composting conditions. The biodegradation rate of the biodegradable composite polylactic acid packaging bag under soil conditions reaches 18.2% in 180 days and a 1-year biodegradation rate of 18.2%. The biodegradation rate in 2 years reaches 44.2%, and the biodegradation rate in 2 years reaches 97.1%. All performance parameters are better than those of the comparative example, which shows that the present invention uses isophorone diisocyanate as a cross-linking agent to prepare polylactic acid, polyethylene glycol, and hexamethyl-1,15-dihydroxyoctasiloxane multi-block copolymerized cross-linked modified polylactic acid as a basic raw material, uses modified starch modified by high temperature of glycerol and chitosan reinforced cellulose-rich wood chip fibers as reinforcing materials, and uses pigments and additives as auxiliary additives, which not only effectively improves the mechanical strength and high temperature resistance of the packaging bag material, but also improves the biodegradability of the packaging bag.

[0124] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0125] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0126] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A biodegradable composite polylactic acid packaging bag, characterized in that: The invention comprises the following components in parts by weight: 90-100 parts of modified polylactic acid, 10-15 parts of modified starch, 15-20 parts of modified nanofibers, 4-8 parts of pigments and 5-7 parts of additives; The preparation method of the modified polylactic acid is as follows: L-lactide, polyethylene glycol, hexamethyl-1,15-dihydroxyoctasiloxane, toluene and a catalyst are added into a nitrogen-protected reactor and stirred, the jacket temperature of the reactor is increased to 120-130° C., the reactor is kept warm for reaction for 8-10 hours, the reactor temperature is reduced to 75-85° C., isophorone diisocyanate is added into the reactor, the reactor is kept warm for 3-4 hours, and the modified polylactic acid is obtained by post-processing.

2. The biodegradable composite polylactic acid packaging bag according to claim 1, characterized in that: The amount ratio of L-lactide, polyethylene glycol, hexamethyl-1,15-dihydroxyoctasiloxane, toluene, catalyst and isophorone diisocyanate is 28-32g:5-7g:8-10g:300mL:0.5g:6-8g, the catalyst is stannous octoate, and the polyethylene glycol is polyethylene glycol 200.

3. The biodegradable composite polylactic acid packaging bag according to claim 1, characterized in that: The preparation method of modified starch is as follows: adding starch and glycerol into a torque rheometer at a temperature of 120-130° C., setting the stirring speed to 70-80 r / min, heat preservation for 15-25 minutes, cooling and discharging the material to obtain modified starch.

4. The biodegradable composite polylactic acid packaging bag according to claim 3, characterized in that: The weight ratio of the starch to glycerol is 7:2-3, and the starch is one or more of sweet potato starch, potato starch, and cassava starch.

5. The biodegradable composite polylactic acid packaging bag according to claim 1, characterized in that: The modified nanofibers are obtained by the following steps: A1, adding sawdust fiber, chitosan and purified water into a ball mill, ball milling for 60-80 minutes, transferring it to a high-pressure homogenizer, homogenizing it for 8-10 times, and post-processing to obtain composite nanofibers; A2. Add the composite nanofibers, anhydrous ethanol and KH-560 into a reactor and stir. The temperature of the reactor is raised to 50-60° C., and sodium hydroxide solution is added into the reactor. The reaction is kept warm for 2-3 hours, and the modified nanofibers are obtained by post-treatment.

6. The biodegradable composite polylactic acid packaging bag according to claim 5, characterized in that: In step A1, the amount ratio of the sawdust fiber, chitosan and purified water is 5g:3g:20mL, and the post-treatment includes: after the treatment is completed, taking it out from the homogenizer, placing it in a freeze dryer at a temperature of -20°C, and freeze-drying to constant weight to obtain composite nanofibers; in step A2, the amount ratio of the composite nanofibers, anhydrous ethanol, KH-560 and sodium hydroxide solution is 7g:30mL:3g:10mL, and the concentration of the sodium hydroxide solution is 0.3-0.5mol / L.

7. The biodegradable composite polylactic acid packaging bag according to claim 5, characterized in that: Wood chip fiber is processed by the following steps: B1. Circulate and extract the sawdust using an extracting liquid at a temperature of 50-60°C for 6-8 hours, and then post-treat the sawdust to obtain pre-treated sawdust; B2, adding the pretreated sawdust, purified water and mixed acid into a nitrogen-protected reactor and stirring, raising the reactor temperature to 70-80°C, and heat-insulating for 6-8h, adding supplementary acid to the reactor once every 50-60min during the heat-insulating stage, and post-treating to obtain acid-treated sawdust; B3, adding acid-treated sawdust and alkali solution into a reactor and stirring, raising the temperature of the reactor to 85-95°C, keeping the temperature and stirring for 3-4 hours, and post-treating to obtain sawdust fiber precursor; B4. Repeat steps B2-B3 to cyclically treat the sawdust fiber precursor 3-4 times to obtain sawdust fibers.

8. The biodegradable composite polylactic acid packaging bag according to claim 7, characterized in that: In step B1, the ratio of sawdust to extract is 1g:10-15mL, and the extract consists of toluene and methanol in a volume ratio of 5:3; in step B2, the ratio of pretreated sawdust, purified water, mixed acid and supplementary acid is 5g:150mL:3g:3g, and the mixed acid and supplementary acid are both composed of sodium chlorite and 80wt% acetic acid aqueous solution in a weight ratio of 1.4:1; in step B3, the ratio of acid-treated sawdust to alkali solution is 1g:15mL, and the alkali solution is 4-7wt% potassium hydroxide aqueous solution.

9. The method for preparing a biodegradable composite polylactic acid packaging bag according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, adding modified polylactic acid, modified starch, modified nanofiber, pigment and additives into a flat yarn machine, heating and plasticizing through a material pipe, extruding and stretching, and obtaining a textile flat yarn; S2, adding the textile flat yarn into a weaving machine for warp and weft weaving to obtain a packaging bag blank, and performing slitting and sewing operations on the bottom opening of the packaging bag blank to obtain a packaging bag.

10. The method for preparing a biodegradable composite polylactic acid packaging bag according to claim 9, characterized in that: In step S1, the additive is composed of a dispersant, an antioxidant, a light stabilizer, an antistatic agent, and a plasticizer in a weight ratio of 2:1:2:1:4, the dispersant is stearate, the antioxidant is one or more of antioxidant 168, antioxidant 364, and antioxidant 1010, the light stabilizer is one or more of UV-944, UV-770, and UV-783, the antistatic agent is sodium p-nonylphenoxypropyl sulfonate, and the plasticizer is phthalate. The temperatures of the eight temperature sections of the material pipe of the flat wire machine from the feed end to the discharge end are 175-185°C, 180-190°C, 185-195°C, 185-195°C, 185-195°C, 185-195°C, 190-200°C, and 190-200°C, respectively, and the stretching ratio is 5-7 times.

Citation Information

Patent Citations

  • Biodegradable PP (polypropylene) woven bag material and preparation method thereof

    CN108586934A

Cited By

  • Polyester composition as well as preparation method and application thereof

    CN121628317A